2020
DOI: 10.1590/1980-5918.033.ao12
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stretching on muscle morphometry of ovariectomized rats

Abstract: Efeitos do alongamento na morfometria do músculo em ratas ovarectomizadasLos efectos del ejercicio de estiramiento en la morfometria muscular de las ratas ovariectomizadas Abstract Introduction: Ageing is responsible for structural alterations, declining of all physiological variables, including range of motion and skeletal muscle function, known as sarcopenia. Objective: The aim of the study was to evaluate the effects of stretching on muscle morphometry in ovariectomized rats. Method: 21 female Wistar rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…After 3 weeks of post-surgery recovery and 1 more week of experiment, a significant increase in body weight was already observed in OVX rats, compared to Sham rats. These results are similar to those of previous studies [6,19,25]. The increase in body weight may be due to hormonal dysfunction and to the greater accumulation of fat as well as to the greater food intake of OVX rats, as observed in the present study [6,10,12,19].…”
Section: Discussionsupporting
confidence: 93%
“…After 3 weeks of post-surgery recovery and 1 more week of experiment, a significant increase in body weight was already observed in OVX rats, compared to Sham rats. These results are similar to those of previous studies [6,19,25]. The increase in body weight may be due to hormonal dysfunction and to the greater accumulation of fat as well as to the greater food intake of OVX rats, as observed in the present study [6,10,12,19].…”
Section: Discussionsupporting
confidence: 93%
“…Conflicting findings occurred when static stretching of the soleus muscle of rats was conducted using a protocol of 1 minute, 10 times per session, 3 times per week for 3 weeks. The results from this animal study found an increase in sarcomeres in series [18]. Specific resistance training protocols were also used to inquire if muscle fiber lengthening occurs.…”
Section: Muscle Componentmentioning
confidence: 70%
“…with resistance exercise at joint end-range [19] and eccentric strengthening exercise [20][21][22]. It appears the muscle is adapting to provide a more optimal length-tension relationship which requires greater length that may be explained by an The Asian Journal of Kinesiology | Asian J Kinesiol 2022; 24(4): [16][17][18][19][20][21][22][23][24] • DOI: https://doi.org/10.15758/ajk.2022. 24.4.16 addition of sarcomeres in series.…”
Section: Muscle Componentmentioning
confidence: 99%
See 2 more Smart Citations